Exploring the Role of Tiktok Content: Influencer Strategies in Increasing Consumer Trust in Products on Shopee - I Nyoman Mertha dana; Nyoman Dwika Ayu Amrita (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Abstract The internet has opened up new opportunities for consumer behavior, including online shopping. A phenomenon that has attracted attention in this study is the role of TikTok content in influencing consumer trust levels in one of Indonesia's leading e-commerce platforms, Shopee. The purpose of this study is to conduct a comprehensive literature review on the role of influencer marketing in the context of Exploring the Role of TikTok Content: Influencer Strategies in Increasing Consumer Trust in Products on Shopee. The analysis results show that consumers are more likely to perceive influencers as truly trustworthy in assessing the positive characteristics of a product. Consumers will view brands and products more favorably through endorsements from people they consider credible. Utilizing marketing strategies through the Shopee Affiliate program on TikTok has proven effective in increasing purchase interest in Shopee products. This strategy can be a relevant option for industry players in reaching consumers by presenting content that aligns with their digital lifestyles and consumption patterns on social media platforms. Keywords: Influencer, TikTok, Shopee, Credibility, Trust